2002
DOI: 10.1080/15226510208500075
|View full text |Cite
|
Sign up to set email alerts
|

Phytoaccumulation and Phytotoxicity of Cadmium and Chromium in DuckweedWolffia globosa

Abstract: The phytoaccumulation and phytotoxicity of heavy metals, cadmium (Cd), and chromium (Cr) on a common duckweed, Wolffia globosa, were studied. W. globosa were cultured in 3% Hoagland's nutrient medium, which was supplemented with 1, 2, 4, and 8 mg/L of Cd and Cr and were separately harvested after 3, 6, 9, and 12 days. The accumulation of Cd and Cr in W. globosa showed significant increases when the exposure time and metal concentration were increased. The effects of Cd and Cr on the biomass productivity and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(30 citation statements)
references
References 28 publications
3
26
0
1
Order By: Relevance
“…Several studies also showed similar results, such as a reduction in growth of bean plants treated at 96 hours with 5 µM of Cd and 100 µM of Zn 26 , a decrease in biomass of pea plants treated with 4 and 40 µM of Cd in hydroponic culture for 7 days 27 , and a decrease in biomass of duckweed treated with Cd at 1, 2, 4 and 8 mg/L with increasing concentration and exposure time 28 .…”
Section: Scienceasia Scienceasia Scienceasiasupporting
confidence: 52%
“…Several studies also showed similar results, such as a reduction in growth of bean plants treated at 96 hours with 5 µM of Cd and 100 µM of Zn 26 , a decrease in biomass of pea plants treated with 4 and 40 µM of Cd in hydroponic culture for 7 days 27 , and a decrease in biomass of duckweed treated with Cd at 1, 2, 4 and 8 mg/L with increasing concentration and exposure time 28 .…”
Section: Scienceasia Scienceasia Scienceasiasupporting
confidence: 52%
“…When expressed by mg Cr per kg plant dry weight, the Cr uptake rate by plants was highly correlated with Cr concentraions in the hydroponic solution as shown in Fig. 2 (the linear trend line and the R-square value are given), which agreed with others Boonyapookana et al 2002;Aldrich et al 2003). The mass balance for total Cr Cr contents in the various plant compartments are presented in Fig.…”
Section: Effects Of Cr 6+ On the Activities Of Antioxidant Enzymes Inmentioning
confidence: 72%
“…Phytoextraction is a process of assimilating soil pollutants and subsequent translocation to harvestable plant parts (Kumar et al 1995). A number of works have been focused on Cr bioaccumulation with emphasis on the selection of hyperaccumulator species of plants Boonyapookana et al 2002;Aldrich et al 2003;Zayed and Terry 2003). Most plants selected belong to either grasses or cultivated species, which directly serve as food sources for numerous higher animals.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in whole plants, both the photosystems were affected. Chromium stress can induce three Environ Chem Lett (2010) 8:199-216 207 possible types of metabolic modification in plants: (i) alteration in the production of pigments, which are involved in the life sustenance of plants (e.g., chlorophyll, anthocyanin) (Boonyapookana et al 2002) (ii) increased production of metabolites (e.g., glutathione, ascorbic acid) as a direct response to Cr stress, which may cause damage to the plants (Shanker et al 2003b) and (iii) alterations in the metabolic pool to channelise the production of new biochemically related metabolites, which may confer resistance or tolerance to Cr stress (e.g., phytochelatins, histidine) (Schmfger 2001). Induction and activation of superoxide dismutase (SOD) and of antioxidant catalase are some of the major metal detoxification mechanisms in plants (Shanker et al 2003a).…”
Section: Chromium Effects On Plantsmentioning
confidence: 99%